Nutritional Stress Induced by Amino Acid Starvation Results in Changes for Slc38 Transporters in Immortalized Hypothalamic Neuronal Cells and Primary Cortex Cells - Hellsten, Sofie V.; Tripathi, Rekha; Ceder, Mikaela M.; Fredriksson, Robert (Frontiers in Molecular Biosciences, 2018)
Amino acid sensing and signalling is vital for cells, and both gene expression and protein levels of amino acid transporters are regulated in response to amino acid availability. Here, the aim was to study the regulation of all members of the SLC38 amino acid transporter family, Slc38a1-11, in mouse brain cells following amino acid starvation. We reanalyzed microarray data for the immortalized hypothalamic cell line N25/2 subjected to complete amino acid starvation for 1 h, 2 h, 3 h, 5 h or 16 h, focusing specifically on the SLC38 family. All 11 Slc38 genes were expressed in the cell line, and Slc38a1, Slc38a2 and Slc38a7 were significantly upregulated at 5 h and most strongly at 16 h. Here, protein level changes were measured for SLC38A7 and the orphan family member SLC38A11 which has not been studied under different amino acid starvation condition at protein level. At 5 h, no significant alteration on protein level for either SLC38A7 or SLC38A11 could be detected. In addition, primary embryonic cortex cells were deprived of nine amino acids, the most common amino acids transported by the SLC38 family members, for 3 h, 7 h or 12 h, and the gene expression was measured using qPCR. Slc38a1, Slc38a2, Slc38a5, Slc38a6, Slc38a9 and Slc38a10 were upregulated, while Slc38a3 and Slc38a7 were downregulated. Slc38a8 was upregulated at 5 h and downregulated at 12 h. In conclusion, several members from the SLC38 family are regulated depending on amino acid levels and are likely to be involved in amino acid sensing and signalling in brain.